Homeopathy for Heteropathy: FSS and Its Components for the Treatment of Alzheimer’s Disease and Endometriosis - Yu Y; Sun T; Zhang J; Wu S; Tong X; Zhao F; Fu X (Drug Design, Development and Therapy)
Yang Yu,1 Tiantian Sun,2 Jingyu Zhang,2 Songquan Wu,1 Xin Tong,3 Fazheng Zhao,3 Xin Fu1 1School of Medicine, Lishui University, Lishui, 323000, Zhejiang Province, People’s Republic of China; 2School of Pharmacy, Heilongjiang University of Chinese Medicine, Harbin, 150040, Heilongjiang Province, People’s Republic of China; 3Zhejiang University of Traditional Chinese Medicine, Hangzhou, 310000, Zhejiang Province, People’s Republic of ChinaCorrespondence: Xin Fu, Email fu19511317872@sina.comAbstract: Foshou San (FSS), which is a traditional Chinese compound formula. So far, a variety of components have been isolated and identified from its complex composition. These findings endow it with diverse pharmacological activities. According to a number of studies, FSS has significant efficacy in treating cognitive impairment in Alzheimer’s disease (AD) and gynecological diseases like Endometriosis (EMs). Behind these curative effects, the specific chemical components of FSS play a crucial role. In this paper, the research progress of FSS in phytochemistry, pharmacology and pharmacokinetics are reviewed. Through comprehensive analysis of apoptosis regulation, oxidative stress and inflammation, ferroptosis, bile acid and intestinal flora, we further demonstrate the feasibility and potential of FSS in treating of AD and EMs. This not only reveals the potential mechanism of FSS, but also provides valuable experience and enlightenment for future research and application in related fields.Keywords: Foshou San, component, alzheimer’s disease, endometriosis, homeopathy for heteropathy